The role of autophagy activation-mediated by Let-7 in a transgenic mouse model of Machado-Joseph Disease - Estremores, Beatriz Filipa Varela (2018)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia